Educação em saúde: Efeito de um método de auto-instruçáo sobre os níveis de higiene oral em escolares - Garcia, Patricia Petromilli Nordi Sasso [UNESP] (2009)
Objective: To identify the effect of a self-instructive method (comic strip), applied with distinct approaches and evaluated over two periods, on the oral health of schoolchildren. Method: The sample comprised 2nd year elementary schoolchildren chosen randomly and divided into four groups: a control group (G1) which received no material, a reading group (G2), which was given the comic strip and read it in the classroom, a discussion group (G3), who received the comic strip, which was read out loud in the classroom and discussed, and a complete group (G4), which received the comic strip and which, after reading it, was asked to rewrite the story. O'Leary's plaque index was used as an evaluation instrument, measured immediately prior to application of the program and again 30 days later. The plaque index measured after and 30 days was compared, in each group, using the Wilcoxon test. The plaque index of the diferents groups was compared using the Kruskal-Walis test, in two moments diferents. The significance level was 5%. Results: The results of the evaluation revealed a statistically significant reduction (p<0.05) of the plaque index presented between the two periods in the four groups studied here. However, this reduction was considerably greater in the discussion and complete groups. Conclusion: The use of the self-instruction method associated with work on its content, as occurred in the discussion and complete groups, led to a better understanding of the subject matter, resulting in a higher reduction of plaque indices.